Lithium Batteries: Stable Nano‐Encapsulation of Lithium Through Seed‐Free Selective Deposition for High‐Performance Li Battery Anodes (Adv. Energy Mater. 7/2020). Issue 7 (18th February 2020) - Ye, Weibin; Pei, Fei; Lan, Xiangna; Cheng, Yong; Fang, Xiaoliang; Zhang, Qiaobao; Zheng, Nanfeng; Peng, Dong‐Liang; Wang, Ming‐Sheng
Abstract : In article number 1902956, Ming‐Sheng Wang and co‐workers demonstrate the concept of nanoencapsulation of Li metal via seed‐free Li deposition inside carbon nanospheres by in situ electron microscopy. Such spheres enable Li filling in a highly reversible and repeatable manner, achieving dendrite‐free battery anodes with high cycling performance.